The impact of gel fingernail polish application on the reduction of bacterial viability following a surgical hand scrub. Issue 7 (3rd August 2021) - Anderson, Stacy L.; Wisnieski, Lauren; Achilles, Stephanie L.; Wooton, Kaitlyn E.; Shaffer, Carrie L.; Hunt, Julie A.
Abstract: Objective: To determine the effect of gel nail polish application on the reduction of bacterial viability immediately after a surgical hand scrub. Study Design: Randomized controlled trial. Sample Population: Ten fingernails each from 40 female health care professionals and students. Methods: Participants' fingernails were randomized to receive no polish or gel nail polish during a manicure from a licensed manicurist. One day and 14 days after manicure, participants' fingernails were sampled before and after a surgical hand scrub with chlorhexidine gluconate. The samples for each fingernail were serially diluted, plated on a Trypsin sheep blood agar and MacConkey's agar plate, and incubated for 36 h. For each plate, bacterial colony forming units (CFU)/ml were determined. Mixed linear models were used to assess factors associated with the logarithmic reduction of viable bacterial counts from pre‐ to post‐surgical scrub. Results: In the final model, no association was detected between gel nail polish and reduction of viable bacterial count ( p  = .09). On Day 14, among longer nail lengths (2 to <3‐mm and ≥3‐mm), surgical scrubs resulted in greater reduction in bacterial counts in left‐handed than right‐handed participants ( p  < .01). Increasing nail length was correlated with increased CFU/ml post‐scrubbing ( p  < .001). Conclusion: Application of gel nail polish did not seem to affect the ability of surgical scrub to reduce bacterial viability 1 and 14 days after a manicure. Clinical Impact: This study does not provide evidence to prevent application of gel nail polish on short fingernails in surgeons prior to surgical hand scrub with chlorhexidine gluconate.